AMBIGUITAS BENTUK AKTA NOTARIS (ANALISIS UNDANG-UNDANG TENTANG JABATAN NOTARIS DAN KITAB UNDANG-UNDANG HUKUM PERDATA) (Lex Jurnalica, 2018)
AbstractThis study aims to understand whether the form of a notary deed in the law concerning the position of a notary (UUJN) fulfills the provisions of Article 1868 of the Civil Code (KUHPerdata) concerning authentic deeds. In order to achieve this goal, a normative analytical descriptive juridical research method is used to provide an overview of legal relations Article 38 UUJN with Article 1868 of the Civil Code as the legal basis for making authentic deeds.This method produces research that the form of a notary deed in Article 1868 of the Civil Code is not regulated in UUJN, which means the UUJN does not regulate the nature of the notary deed, causing ambiguity in the form of notary deed. Keywords: ambiguity, form, notary deed                    AbstrakPenelitian ini bertujuan memahami apakah bentuk akta notaris dalam undang-undang tentang jabatan notaris (UUJN) memenuhi ketentuan Pasal 1868 Kitab Undang-Undang Hukum Perdata (KUHPerdata) mengenai akta otentik. Dalam rangka mencapai tujuan ini digunakan metode penelitian yuridis normatif yang bersifat deskriptif analitis guna memberikan gambaran hubungan hukum Pasal 38 UUJN dengan Pasal 1868 KUHPerdata sebagai dasar hukum dalam pembuatan akta otentik. Metode ini menghasilkan penelitian bahwa bentuk akta notaris dalam Pasal 1868 KUHPerdata tidak diatur dalam UUJN, yang berarti UUJN tidak mengatur sifat akta notaris sehingga menyebabkan ambiguitas bentuk akta notaris. Kata kunci: ambiguitas, bentuk, akta notaris